Efektivitas Pogram Pusat Pembelajaran Keluarga (PUSPAGA) dalam Wujudkan Pola Pengasuhan Anak di Kelurahan Genting Kalianak Kecamatan Asemrowo Kota Surabaya Jawa Timur - Rofifah Ismah Larasati; Radjikan Radjikan (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Parents occupy the main position and take full responsibility in Parenting Children and Families. Generally the family as the first environment present in every Individual who has been born in the world, the Family Environment includes Father, Mother and Child itself. The relationship between parents and their children is one of the relationships that are present intertwined. Parenting is an interaction between children and parents which not only includes physical or psychological, but also established norms that will apply in community life so that life becomes in harmony with the surrounding environment (Gunarsa, 2000). However, the situation of parenting patterns that exist between parents and children is still concerning, such as the lack of understanding of parents in educating and paying attention to children's growth and development, this makes it difficult for children to know the outside world and becomes a barrier to the survival and growth of children's lives. PUSPAGA (Family Learning Center) plays a leading role in prevention and parenting among the community. This study uses a qualitative approach method with a descriptive type of research, the purpose of this study is to determine the effectiveness of the Puspaga program in realizing childcare patterns in Genting Kalianak Village, Asemrowo District, Surabaya City, the data collection process uses interviews, observation, documentation and the internet. The results showed that in the early stages where there were problems in parenting patterns. In child care as referred to in paragraph (1), it is carried out through continuous guidance, maintenance, care, and education activities, as well as by providing financial assistance and/or other facilities, to ensure optimal child growth and development, both physically, mentally, spiritually and socially, without affecting the child's religion (PP 44, 2017).